"Auctoritas" and "potestas" as a metaphor for the bishop’s role models in the canons of the Councils of Toledo of the 7th century - Mikhail Birkin (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
The article is concerned with the key medieval opposition between auctoritas and potestas. It is explored in connection with the figure of the bishop as mainly exemplified in the canons of the Councils of Toledo. Since these words were not attributed to secular or ecclesiastical authority alone, a brief overview of the word usage is first given. Firstly, it made possible to specify the interaction between royal power and the Church, for which secular power was understood as alien. Secondly, examples of the non-technical use of the terms auctoritas and potestas in relation to the bishop have been detected. These cases are then examined. The author briefly retraces the continuity of the Roman notion of auctoritas in relation to the authority of the bishop (mature age, experience, eloquence, euergetism, reputation based among others on such right qualities as grauitas, prudentia, probitas etc.). As in Roman period, the auctoritas of the bishop means above all his power of persuasion, therefore his main management tools were preaching and admonition (sacerdotalis admonitio). The subordinates were supposed to take the path of correction by their will (uoluntas propria). If the bishop lacked authority, he could resort to various types of punishment (animaduersio sacerdotalis). Animaduersio sacerdotalis was linked to the potestas concept. The author suggests that the words auctoritas and potestas could be used as metaphors for describing the bishop's role models. If potestas model, relatable to the sphere of the secular, prevailed, this could cause destruction of the community as a sacralized small community where relationships were to be based on consensus reached non-violently. These observations help to clarify the widespread statement that since the fifth century auctoritas was supposedly connected only with spiritual power and potestas with secular power.